MANAGEMENT OF BENIGN FIBROUS HISTIOCYTOMA AT SULTAN FATAH DEMAK HOSPITAL - Amiza Zam, Syarifah Nova; Agustin, Aisyah Nafa; Faadhila, Annisa Husna; Annsya, Resty; Fahrie, Thania Olivia; Lathifa, Ovie Luksita (Universitas Muhammadiyah Semarang, 2024)
Benign Fibrous Histiocytoma (BFH) is a benign soft tissue tumor consisting of fibroblastic and histiocytic cells. The most often affected locations by BFH lesions are the buccal mucosa, mandibular bones, gingiva, lower and upper lips, soft palate, and floor of the mouth. The etiology of BFH is unknown, but the etiology is thought to be reactive changes from previous infections such as insect bites or thorn pricks. Signs and symptoms of BFH include round-shaped swelling, appearing reddish at first, and turning brown. Case: A 40 year old male patient came to the Sultan Fatah Regional Hospital Demak with complaints of swelling of the left cheek below the eye, dizziness and fever for the last 7 days. Patients eat and drink with bread mixed in water or tea. The patient came in a compos mentis state, but the patient was less cooperative. Case management: The patient underwent incision and drainage. Tissue was taken for biopsy examination measuring 1 x 0.4 x 0.3 cm. The patient follow-up was carried out 7 days after the procedure. Results: Follow-up at 7 days after the procedure showed the patient's mouth opening was 1 cm. Conclusion: In this case, from subjective, objective, and supporting examinations, cause of infection has not been found. The treatment carried out is incision and drainage of the infection.